2022
DOI: 10.1177/1097184x221098723
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Lifetime Perpetration of Intimate Partner Violence Among Ever-Partnered Men in South Sudan

Abstract: Intimate partner violence (IPV) is the most common form of violence against women and girls (VAWG). Research has shown that gender inequitable attitudes, economic stressors, and armed conflict are among the many risk factors for IPV. Armed conflict can leave women and girls even more vulnerable to gender-based violence and create a context in which hegemonic masculinity may escalate different forms of VAWG. In South Sudan, a country that has been affected by continued armed conflicts, more than half of ever-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…"Sometimes people do things outside of their relationship, so it ends up being violent because men sometimes do not know how to handle that type of a situation. Instead of walking away or maybe try sit and find out what is happening, they rather take it upon themselves and start being violent trying to fix the situation"-Amo, 31…”
Section: Insecurities Infidelity and Gbvmentioning
confidence: 99%
See 1 more Smart Citation
“…"Sometimes people do things outside of their relationship, so it ends up being violent because men sometimes do not know how to handle that type of a situation. Instead of walking away or maybe try sit and find out what is happening, they rather take it upon themselves and start being violent trying to fix the situation"-Amo, 31…”
Section: Insecurities Infidelity and Gbvmentioning
confidence: 99%
“…The study further revealed men's stereotyped view that a woman cannot decline sexual intercourse with her husband, and that she should make it her obligation to prevent falling pregnant. Various authors are in agreement in that inequitable power distribution across genders render women vulnerable to violence by men, in the name of discipline or maintenance of order in their home [29][30][31].…”
mentioning
confidence: 99%